Response of Soybean Plants Cv. Shaima to NPK Fertilizer and Locally Produced Nano-Iron - Al-tamimi , Idrees Ghalib Idrees; Maizar , Noora Bandar; Salim , Hussein Ali; Abed , Mohammed Saheb (American Journal of Biology and Natural Sciences, 2026)
An assay was carried out in the Research Station, Agricultural Extension and Training Center in Diyala in the season 2023 to study the response of soybean plants cv. Shaima to NPK fertilizer and locally produced nano-iron. A factorial experiment in a complete randomized block design was used, included two factors; the first factor included chemical fertilizer NPK at three levels (no addition, half the fertilizer recommendation, full recommendation), and the second factor included nano-iron fertilizer at three levels (no addition, half the fertilizer recommendation, full recommendation). The treatment of the full recommendation of NPK fertilizer and nano-iron performed better in most of the traits represented with plant height, leaf area, number of pods, dry shoot weight, iron concentration in leaves, nitrogen, and potassium, which reached 58.9 cm, 33.1 dcm, 47.0, 34.1 g, 98.4 ppm, 5.2%, and 4.3%, respectively. The full recommendation of NPK resulted in an increase in the total yield, reaching 3.8 tons ha-1, compared to the control treatment of 3.0 tons ha.